Konflik Tapal Batas antara Desa Tanjung Telang dengan Kelurahan Payuputat Kecamatan Prabumulih Barat Kota Prabumulih - Minako, Muchlis; Savella, Rizky (Indonesian Journal of Social Development, 2023)
This research is entitled "Border Conflict Between Tanjung Telang Village and Payuputat Village, West Prabumulih District, Prabumulih City". The problem with this research is why it happened Boundary conflict between Tanjung Telang Village and Payuputat Village and resolution of the conflict. The purpose of this study is to explain the occurrence of boundary conflicts between the village of Tanjung Telang and Kelurahan Payuputat, West Prabumulih District, Prabumulih City. This research is a qualitative research whose unit of analysis is the people of Tanjung Telang and Payuputat villages. Data collected by direct observation, in-depth interviews with informants. The research method used is qualitative which consists of three activity streams, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that the conflict occurred at the border crossing between the village of Tanjung Telang and the village of Payuputat due to several factors, namely the first historical factor, the second factor of different perceptions, and three economic factors.